An accelerometer based-feedback technique for improving dynamic performance of a machine tool - Abir, Jonathan; Morantz, Paul; Longo, Stefano; Shore, Paul (European Society for Precision Engineering and Nanotechnology, 2016)
A novel concept for improving machine dynamic performance was developed and realised, a virtual metrology frame, for a small size CNC machine with flexible frame. Its implementation in a simplified linear motion system shows a reduction in the magnitude of the first resonance in the plant frequency response function by 12 dB. Realising the concept required developing a real -time accelerometer-based measurement technique. It shows a low sensor noise σ=30 nm with optimal phase delay of <70 μs.
Keywords: Accelerometer; mechatronic; compact machine; flexible frame; flexible frame; virtual metrology frame; genetic algorithm